Análisis biomecánico de la influencia del calzado deportivo en los esfuerzos presentes en la extremidad inferior (2015)
The aim of this study is to perform a biomechanical analysis of the influence of sports shoes in the present efforts in the lower extremity during the phase of support in the cycle of the trot. To do this, a description For this reason, the aim of this study is to perform a biomechanical analysis of the influence of sports shoes in the present efforts in the lower extremity during the phase of support in the cycle of the trot. To do this, a description of the distribution of mechanical stress on the joints of the lower limb in the presence and absence of the intermediate template (midsole) for sports shoes, by means of a finite element analysis. It was subsequently obtained the Von Mises stress for the conditions of trot barefoot and trot with use of the template of the staff.